A Seasonal Arima Model for Daily Nigerian Naira-Us Dollar Exchange Rates - Etuk, Ette Harrison (Asian Journal of Empirical Research, 2012)
Time series analysis of daily Nigerian Naira-US Dollar Exchange Rates (DNDER) data is conducted. The time plot reveals a positive trend. Seasonality of order 7 is observed; troughs tend to appear on Mondays and peaks on Fridays. Seasonal differencing once produced a series SDDNDER with a slightly overall negative trend. A non-seasonal differencing of SDDNDER yielded a series DSDDNDER with no trend but with a correlogram revealing seasonality of order 7. Moreover, the correlogram reveals the involvement of a seasonal moving average component of order 1 and a nonseasonal autoregressive component of order 2. An adequate multiplicative seasonal autoregressive integrated moving average (ARIMA) model, (2, 1, 0)x(0, 1, 1)7, is therefore fitted to the series.